The first triple-decker complex with the PtMe3 fragment: CpCo([mu]-1,3-C3B2Me5)PtMe3 - Romanov, Alexander S.; Siebert, Walter (Mendeleev communications, 2012)
The μ-diborolyl triple-decker complex CpCo(μ-1,3-C3B2Me5)PtMe3 was prepared by reaction of the sandwich anion [CpCo(1,3-C3B2Me5)]-with [PtMe3I]4; according to energy decomposition analysis, attractive interactions between the [CpCo(1,3-C3B2Me5)]- and [PtMe3]+ fragments are ∼64% electrostatic and 36% covalent.
Im Titel ist mu als griechischer Buchstabe dargestellt
Gesehen am 11.04.2018